O fitoplâncton como instrumento de biomonitoramento da qualidade da água do Reservatório de Cachoeira Dourada - Rio Paranaíba - GO/MG - Oliveira, Márcia Teixeira de (2010)
The phytoplankton community is one of the communities recommended as a tool for evaluations of water quality. The relevance of ecological and sanitary studies of phytoplankton to public health is due to the fact that they attest to water quality and allow waters to be monitored for multiple uses, especially those linked directly to human health. The phytoplankton community of the Cachoeira Dourada reservoir was characterized in the months of December 2006, May 2007 and November 2007 at five sampling points, four of them in the reservoir and one downstream. The phytoplankton sampling, which was based on the principles of the AquaRAP, aimed to evaluate water quality using indices based on physical, chemical and biological characteristics, with emphasis on the phytoplankton community. The results revealed that the phytoplankton was dominated by cyanobacteria in the three sampling periods. Cyanobacteria exhibited higher significance in terms of richness and greater density than the other classes of phytoplankton. Potentially toxic species were represented by Anabaena sp. and Microcystis sp., with higher occurrence during the dry season, albeit in low densities. There was no record of blooming and the analyzed densities lay within the limit established by CONAMA (National Environmental Agency). The reservoir was classified as oligotrophic, based on its phytoplankton diversity, equitability, richness and density. This classification was confirmed by an analysis of the reservoir s physical and chemical variables and by several other indices applied with or without the use of the phytoplankton community. Among the various indices employed, Nygaard s index was the only one considered inefficient in evaluating the trophic degree of the reservoir, because it neglects species density. Phytoflagellates proved to be a good indicator of environments with low transparency (CCA). The main interferents in the reservoir s water quality were found to depend on factors of climate, the dam s operation, and anthropic activities in adjacent areas and in the drainage basin, which were dynamically reflected in the composition and structure of the phytoplankton community in the different periods under study. It is also important to note that the brief residence time of the water is probably the preponderant factor for this oligotrophic state of the reservoir.